Asia in 2025: Development prospects and challenges for middle-income countries - Ganeshan Wignaraja; Judith Tyson; Annalisa Prizzon; Dirk Willem te Velde (Overseas Development Institute (ODI), 2018)
The resilience of developing Asia since the global financial crisis, on top of its historic economic success, has sparked interest in understanding its future. The region is diverse, with sub-regions and countries of varying population size, geography and economic dynamism as well as different vulnerabilities. While the economic performance of many Asian countries remains robust, in 2025 there are also likely to be several middle-income countries (MICs) with persistent pockets of poverty, vulnerability to income shocks and high levels of inequality. This report and briefing note examine the macroeconomic outlook for Asian and Pacific economies and its main drivers, with a focus on the prospects of the region's MICs. The report then offers recommendations for donors and development partners to adapt and tailor their instruments, modalities and approaches to respond to current and future challenges.
Keywords: 330